The Evaluation of Islamic Education of Elementary-Age Children - Ritonga, Asnil Aidah; Ernawati, Tuti (Universitas Pahlawan Tuanku Tambusai, 2022)
Evaluation work related to humans is very much inspired by the Qur'an and is one of the most important tasks in the educational process. The focus in writing this article is evaluation in Islamic education, using a thematic interpretation approach assisted by various literature sources related to evaluation in Islamic education, especially for elementary age children. The results show that evaluation in Islamic education has a very strategic position, because the results of the evaluation can be used as input in improving education, that's why Islam pays so much attention to evaluation, so that there are many verses of the Qur'an related to evaluation.